Rapid repair material for cable well body structure breakage and application method thereof
By using components A and B, the cracked area of the cable well structure is directly filled and extruded, and the existing materials have poor water barrier effect and complex construction are solved, and efficient, durable and economical cable well repair results are achieved.
Patent Information
- Application Number
- CN202411857653.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
The existing cable well structure crushing and repair materials have problems such as poor water barrier effect, easy cracking, complex construction technology, and long material forming time. The cost is high, making it difficult to meet the needs of fast, durable and economical restoration of cable well structures.
A rapid repair material of component A and component B with a mass ratio of 1:1 is used. Component A includes cement clinker, fine aggregate, polymer fiber and retarder. Component B includes aqueous emulsion, water reducer, quick-setting agent and thickener. After stirring and mixing, the crushing area is directly filled, and the interface bonding force is enhanced by geospawn extrusion.
It realizes the crushing and repair of cable wellheads with simple and fast operation, good durability and excellent sealing and filling effect. The material has high bonding strength, compressive strength and tensile strength, and has a wide range of application. No formwork is required for construction, and the strength of the material increases rapidly after initial solidification.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials and relates to a rapid repair material for a broken cable well structure and an application method thereof. Background Art
[0002] With the development of electricity and communications, the amount of underground cable pipelines laid in my country has increased year by year. During the use process, some cable well structures are frequently broken due to improper environmental erosion, such as the hollowing of the cable well mouth, which leads to the failure of the well mouth waterproofing and the worsening of the water accumulation problem in the well. The accumulated water will soak the cable, accelerate the aging of the cable insulation layer, shorten the service life of the cable, and also affect the normal operation of other electrical equipment in the well.
[0003] The cable well structure is often repaired by filling and repairing with traditional materials such as cement mortar, concrete, and red mud. However, traditional materials have poor toughness, easy cracking, and insufficient water-retaining durability in terms of water-retaining effect. In terms of construction technology, there are problems such as poor stacking effect, the need for formwork assistance, and complex process. In addition, there are also a series of problems such as weak bonding force, which makes the interface between the new and old structures weak and easy to fall off again; the material molding time is long, resulting in a long construction period.
[0004] CN109627042A discloses a low-strength high-expansion gelling filling material and a filling method thereof, wherein the filling material is prepared from a matrix component and an external admixture component, wherein the matrix component includes a gelling material and water, and the external admixture component includes a foaming agent, water glass, a water reducing agent, and a foam stabilizer; the foam admixture is 3 to 4 times the volume of the cement slurry, the water glass admixture is 1.0 to 3.0% of the mass of the gelling material, the water reducing agent admixture is 0.5 to 1.0% of the mass of the gelling material, and the foam stabilizer admixture is 0.5 to 1.0% of the mass of the gelling material. The filling material can be applied to the filling of the cavities formed by the collapse of the roof of the goaf of a coal mine, and the space of the old goaf of the working face to prevent gas leakage and accumulation, and to form effective support for the roof of the goaf or goaf to ensure safe production in the mine. This material has a high expansion ratio and fast forming speed, and can quickly fill various irregular broken structures. However, because it relies on a large expansion ratio to implement filling, a formwork must be used to limit the expansion area of the material, which can easily cause a large amount of material waste and pollute the on-site construction environment during the cable well structure repair process. Moreover, this type of material only fills the gap and has no mechanical or bonding effects. It is easily washed away by water pressure during water seepage and has insufficient durability.
[0005] CN108659201A discloses temporary support materials for broken formations during hole enlargement construction by a raise drilling rig, which are composed of material A and material B stored independently of each other; material A is composed of MN-500 polyether polyol, DL-400 polyether polyol, DL-1000D polyether polyol, diisopropylnaphthalene, a catalyst and an ultraviolet absorber; material B is composed of 44V20L isocyanate, modified isocyanate, diisopropylnaphthalene and carbon black. During the hole enlargement construction by the raise drilling rig, the hole enlargement drilling is stopped after the hole enlargement of the target broken formation is completed; material A and material B are input into the nozzle located in the wellbore of the broken formation through different fluid channels for mixing, and then sprayed on the surrounding rock surface of the well wall of the broken formation, material A and material B react rapidly and solidify, thereby forming a support body to improve the surrounding rock conditions of the well wall, playing the role of water stopping and sealing the surrounding rock. This type of material has high strength and strong bonding force, which is beneficial to the restoration of the structure. However, it is usually used in the form of grouting. The viscosity of the slurry is low before solidification. When the formwork is not dense, the accumulation is extremely poor, which is not suitable for the repair of broken cable well structures. In addition, the high cost is also a key factor limiting its application. Summary of the invention
[0006] The purpose of the present invention is to provide a rapid repair material for a broken cable well structure and an application method thereof. By fully mixing the two components A and B, the material can be directly filled into the broken area using tools such as a geotechnical shovel, and quickly bonded to the cable well structure to form a whole, thereby restoring the water retaining function. The operation is simple and quick, and the effect is beautiful.
[0007] The present invention discloses a rapid repair material for a broken cable well structure, comprising: a component A and a component B in a mass ratio of 1:1; wherein the component A comprises, by mass, 40-85 parts of cement clinker, 10-25 parts of fine aggregate, 0.1-0.5 parts of polymer fiber, and 0.1-0.4 parts of retarder; and the component B comprises, by mass, the following raw materials: 70-85 parts of aqueous emulsion, 8-15 parts of water reducer, 1-5 parts of quick-setting agent, and 1-10 parts of thickener.
[0008] Furthermore, the preferred component A comprises, by mass, 78.7-82 parts of cement clinker, 17.5-21 parts of fine aggregate, 0.15-0.25 parts of polymer fiber, and 0.15-0.25 parts of retarder; the preferred component B comprises, by mass, 82-85 parts of aqueous emulsion, 6-8 parts of water reducer, 3-4 parts of accelerator, and 6-8 parts of thickener.
[0009] Furthermore, the fine aggregate is selected from one or more of coal gangue, quartz powder, lime powder (slaked lime) and talcum powder.
[0010] Furthermore, the polymer fiber is selected from one or more of polyethylene fiber, polyvinyl alcohol fiber, polypropylene fiber and aramid fiber.
[0011] Furthermore, the retarder is selected from one or more of tartaric acid, starch, wood calcium, wood sodium, molasses, glucose, sucrose, maltose, starch, and dextrin.
[0012] Furthermore, the aqueous emulsion is selected from one or more of acrylic emulsion, polyvinyl acetate emulsion, ethylene-vinyl acetate emulsion, polypropylene emulsion and styrene-butadiene emulsion.
[0013] Furthermore, the quick-setting agent is selected from one or more of lithium carbonate powder, sodium silicate powder, potassium silicate powder and aluminum sulfate powder.
[0014] Furthermore, the thickener is selected from one or more of porous silica powder, starch, gelatin, pectin, and polyester; preferably selected from one or more of silica powder, gelatin, and polyester.
[0015] Furthermore, the fine aggregate is selected from one or both of lime powder and talcum powder; the retarder includes at least one of starch or dextrin; the thickener includes silicon dioxide, and the thickener also includes gelatin or polyester.
[0016] The present invention also provides an application method of a quick repair material for a broken cable well structure, wherein component A and component B are weighed in equal weight proportions, and stirred in a container until the mixture has no obvious undispersed powder, and the entire slurry is mixed evenly and has a uniform color before use;
[0017] After mixing component A and component B as required, if the repair area is dry / wet but no water seepage is observed, the mixture can be directly filled into the broken area with a geoshovel and squeezed appropriately with a geoshovel to increase the interface bonding strength;
[0018] If there is a small seepage in the repair area, mix the mixture of component A and component B with a small amount of quick-setting cement, and use the quick-setting cement's rapid solidification characteristics when it comes into contact with water to prevent the mixture from being dispersed by the small seepage. The mass ratio of the mixture to quick-setting cement should not be less than 8:1. Too high a dosage of quick-setting cement will significantly reduce the toughness, adhesion and density of the material.
[0019] If there is large seepage in the repair area, grouting or other methods should be used to stop the water, and then this repair material should be used to repair the broken structure.
[0020] The beneficial effects of the present invention are as follows: the repair material is a cable wellhead broken repair material which is convenient and quick to operate, has good durability, excellent sealing and filling effects, and a wide range of applications. The repair material is in a paste state after mixing, has a small slump, and has excellent thixotropic and stacking properties. When the cable well broken height is 20-30 cm, no formwork material needs to be set up; the surface drying time of the stirred slurry is about 5 to 10 minutes, and the initial setting time is about 10 to 30 minutes. After the initial setting, the strength increases rapidly, and it has excellent characteristics such as very high bonding strength (dry concrete base surface, especially wet concrete base surface), very high compressive strength and tensile strength, and certain tensile deformability. DETAILED DESCRIPTION
[0021] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with specific implementation methods, but these descriptions are only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention.
[0022] A quick-repair material for a broken cable well structure, comprising: component A and component B in a mass ratio of 1:1; wherein the component A comprises, by mass, 40-85 parts of cement clinker, 10-25 parts of fine aggregate, 0.1-0.5 parts of polymer fiber, and 0.1-0.4 parts of retarder; and the component B comprises, by mass, the following raw materials: 70-85 parts of aqueous emulsion, 8-15 parts of water reducer, 1-5 parts of quick-setting agent, and 1-10 parts of thickener.
[0023] In particular, the preferred component A of the rapid repair material includes, by mass, 78.7-82 parts of cement clinker, 17.5-21 parts of fine aggregate, 0.15-0.25 parts of polymer fiber, and 0.15-0.25 parts of retarder; the preferred component B includes, by mass, 82-85 parts of aqueous emulsion, 6-8 parts of water reducer, 3-4 parts of accelerator and 6-8 parts of thickener.
[0024] According to component A of the present invention, cement clinker can regulate the gelling time and compressive strength of the repair material, and the cement clinker is selected from one or more of sulphoaluminate cement, silicate cement, aluminate cement, and ferroaluminate cement; preferably selected from one or more of sulphoaluminate cement and silicate cement.
[0025] According to component A of the present invention, the fine aggregate is a powder with a particle size of 500-1000 mesh, which has the function of improving the stacking, fluidity and reactivity of the repair material. The fine aggregate is selected from one or more of coal gangue, quartz powder, lime powder and talcum powder; preferably selected from one or a mixture of talcum powder and lime powder.
[0026] According to component A of the present invention, the toughness of the repair material can be improved by adding polymer fibers, and the polymer fibers are selected from one or more of polyethylene fibers, polyvinyl alcohol fibers, polypropylene fibers, and aramid fibers, preferably one or two of polyvinyl alcohol fibers and polypropylene fibers.
[0027] According to the component A of the present invention, the retarder mainly controls the initial setting reaction time and thickening effect of the repair material slurry, so as to control the construction window time. The retarder is selected from one or more of tartaric acid, starch, wood calcium, wood sodium, molasses, glucose, sucrose, maltose, starch, and dextrin; preferably, it is selected from one or more of starch, dextrin, wood calcium, and wood sodium.
[0028] According to the component B of the present invention, the aqueous emulsion has the function of improving the toughness, density and interfacial adhesion of the repair material on the one hand, and the water in the aqueous emulsion can promote the hydration reaction on the other hand, avoiding the addition of extra water during the application process, which affects the consistency of the material. The aqueous emulsion is selected from one or more of acrylic emulsion, polyvinyl acetate emulsion, ethylene-vinyl acetate emulsion, polypropylene emulsion, styrene-butadiene emulsion; preferably one or two of acrylic emulsion and ethylene-vinyl acetate emulsion with high adhesion and film-forming properties.
[0029] According to the component B of the present invention, an appropriate amount of water reducer is beneficial to improving the strength and stacking properties of the material, and the water reducer is selected from one or more of naphthalene water reducers, aliphatic water reducers and amino water reducers; preferably selected from one or two of naphthalene water reducers and aliphatic water reducers.
[0030] According to the component B of the present invention, the accelerator has the function of accelerating the initial setting and early strength of the repair material, and the catalyst is selected from one or more of lithium carbonate powder, sodium silicate powder, potassium silicate powder, and aluminum sulfate powder; preferably selected from one or two of lithium carbonate powder and sodium silicate powder.
[0031] According to component B of the present invention, adding a thickener can increase the initial viscosity of the repair material and improve the stacking performance. The thickener is selected from one or more of porous silica powder, starch, gelatin, pectin, and polyester; preferably selected from one or more of silica powder, gelatin, and polyester.
[0032] The present invention is further described in detail below in conjunction with embodiments:
[0033] The material compositions of Examples 1-5 and Comparative Examples 1-4 are shown in Table 1 and Table 2
[0034] According to the mass fractions of cement clinker, fine aggregate, polymer fiber and retarder listed in Table 1 below, component A is prepared by uniformly stirring for use.
[0035] Table 1
[0036]
[0037] According to the mass fractions of polymer emulsion, water reducing agent, accelerating setting agent and thickening agent listed in Table 2 below, component B is prepared by stirring evenly for use.
[0038] Table 2
[0039]
[0040]
[0041] Using the components provided in Table 1 and Table 2 and according to the application method provided by the present invention, the performance indicators are listed in Table 3.
[0042] Table 3
[0043]
[0044]
[0045] In Examples 1 to 5, the fine aggregate is lime powder or talcum powder, and the retarder includes at least one of starch or dextrin, and may also include wood calcium and wood sodium, which are used to control the initial setting reaction time and thickening effect of the repair material slurry, so as to control the window time of construction. The aqueous emulsion is selected from one or both of acrylic emulsion and ethylene-vinyl acetate emulsion with high adhesion and film-forming properties. On the one hand, the aqueous emulsion has the effect of improving the toughness, density and interfacial adhesion of the repair material. On the other hand, the water in the aqueous emulsion can promote the hydration reaction, avoid the addition of additional water during the application process, and affect the consistency of the material. The quick-setting agent is selected from one or both of lithium carbonate powder and sodium silicate powder; the thickener is selected from one or more of silica powder, gelatin, and polyester, which can increase the initial viscosity of the repair material and enhance the stacking performance.
[0046] In Comparative Examples 1-3, river sand or mountain sand is selected as fine aggregate, and wood calcium or tartaric acid is used as retarder, resulting in a stacking height much lower than that of Examples 1-5. In Comparative Example 4, lime powder and talcum powder are used as fine aggregate, and the stacking height is improved, but only wood calcium is used as retarder without starch or dextrin, and the stacking height is still not as good as that of Examples 1-5.
[0047] Example 6
[0048] The present embodiment provides an application method of a rapid repair material for a broken cable well structure. According to the formula of any one of Examples 1-5, component A and component B are weighed in equal mass proportions, and stirred in a container until there is no obvious undispersed powder in the mixture, and the entire slurry is evenly mixed and can be used after the color is consistent. It is strictly forbidden to add excessive water during the stirring process. If it is found that there is always a small amount of undispersed powder, the water addition method should be adopted to strictly control the amount of water added. After mixing component A and component B as required, they should be used up quickly within 10 minutes, otherwise the material will dry out and lose its bonding effect;
[0049] If the repair area is dry / wet but no visible water seepage is observed, the rapid repair material (mixture) prepared in Example 6 can be directly picked up with a geoshovel and filled directly into the broken area, and appropriately squeezed with a geoshovel to increase the interface bonding strength;
[0050] If there is a small seepage in the repair area, mix the mixture of component A and component B with a small amount of quick-setting cement, and use the quick-setting cement's rapid solidification characteristics when it comes into contact with water to prevent the mixture from being dispersed by the small seepage. The mass ratio of the mixture to the quick-setting cement should not be less than 8:1. Too high a dosage of quick-setting cement will significantly reduce the toughness, adhesion and density of the material;
[0051] If there is large seepage in the repair area, grouting or other methods should be used to stop the water, and then this repair material should be used to repair the broken structure.
[0052] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A rapid repair material for a broken cable well structure, characterized in that: include: Component A and component B are in a mass ratio of 1:1; wherein the component A comprises, by mass, 40-85 parts of cement clinker, 10-25 parts of fine aggregate, 0.1-0.5 parts of polymer fiber, and 0.1-0.4 parts of retarder; and the component B comprises, by mass, the following raw materials: 70-85 parts of aqueous emulsion, 8-15 parts of water reducing agent, 1-5 parts of accelerating setting agent, and 1-10 parts of thickener.
2. The rapid repair material for broken cable well structure according to claim 1 is characterized in that: Component A comprises, by weight: 78.7-82 parts of cement clinker, 17.5-21 parts of fine aggregate, 0.15-0.25 parts of polymer fiber, and 0.15-0.25 parts of retarder; the preferred component B comprises, by weight: 82-85 parts of aqueous emulsion, 6-8 parts of water reducer, 3-4 parts of accelerator, and 6-8 parts of thickener.
3. The rapid repair material for broken cable well structure according to claim 1, characterized in that: The fine aggregate is selected from one or more of coal gangue, quartz powder, lime powder and talcum powder.
4. The rapid repair material for broken cable well structure according to claim 1, characterized in that: The polymer fiber is selected from one or more of polyethylene fiber, polyvinyl alcohol fiber, polypropylene fiber and aramid fiber.
5. The rapid repair material for broken cable well structure according to claim 1, characterized in that: The retarder is selected from one or more of tartaric acid, starch, wood calcium, wood sodium, molasses, glucose, sucrose, maltose, starch, and dextrin.
6. The rapid repair material for broken cable well structure according to claim 1, characterized in that: The aqueous emulsion is selected from one or more of acrylic emulsion, polyvinyl acetate emulsion, ethylene-vinyl acetate emulsion, polypropylene emulsion and styrene-butadiene emulsion.
7. The rapid repair material for broken cable well structure according to claim 1, characterized in that: The quick-setting agent is selected from one or more of lithium carbonate powder, sodium silicate powder, potassium silicate powder and aluminum sulfate powder.
8. The rapid repair material for broken cable well structure according to claim 1, characterized in that: The thickener is selected from one or more of porous silica powder, starch, gelatin, pectin and polyester.
9. The rapid repair material for broken cable well structure according to claim 2, characterized in that: The fine aggregate is selected from one or both of lime powder and talcum powder; the retarder includes at least one of starch or dextrin; the thickener includes silicon dioxide, and the thickener also includes gelatin or polyester.
10. A method for applying the quick repair material for a broken cable well structure according to any one of claims 1 to 8, characterized in that: Weigh component A and component B in equal weight proportions, stir in a container until there is no obvious undispersed powder in the mixture, and the entire slurry is mixed evenly and has a consistent color before use; After mixing component A and component B as required, if the repair area is dry / wet but no visible water seepage is observed, use a geoshovel to pick up the mixture and fill it directly into the broken area, and use a geoshovel to squeeze it appropriately to increase the interface bonding strength; If there is a small seepage in the repair area, mix the mixture of component A and component B with quick-setting cement, and use the quick-setting cement's rapid solidification characteristics when it comes into contact with water to prevent the mixture from being dispersed by the small seepage; the mass ratio of the mixture to quick-setting cement should not be less than 8:
1. Too high a dosage of quick-setting cement will significantly reduce the toughness, adhesion and density of the material; If there is large seepage in the repair area, this repair material should be used to repair the broken structure after water is stopped.
Citation Information
Patent Citations
Temporary timbering material for broken stratum of raise boring machine chambering construction
CN108659201A
Low-strength high-expansibility gel filling material and filling method thereof
CN109627042A